2019
DOI: 10.1136/neurintsurg-2019-015412
|View full text |Cite
|
Sign up to set email alerts
|

Effect of blood pressure parameters on functional independence in patients with acute ischemic stroke in the first 6 hours after endovascular thrombectomy

Abstract: Background and purposeStudies have suggested that blood pressure (BP) levels after endovascular thrombectomy (EVT) are correlated with clinical outcomes. The aim of our study was to investigate the effect of BP in different time intervals within the first 24 hours after EVT on functional outcomes.MethodsData of patients who received EVT for acute ischemic stroke at two institutions were reviewed. After EVT, hourly BP data were collected and divided into four time intervals: 1–6 hours, 7–12 hours, 13–18 hours, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…Studies concluded the relationship between short‐term systolic BPV and poor clinical outcomes was influenced by recanalization status following EVT, as determined by the modified Thrombolysis in Cerebral Infarction (MTICI) scores. In five separate studies, the association was strongest for patients with successful recanalization (mTICI 2b or 3) 11‐14,17 . However, this is in contrast with both Anadani et al's 7 study, which found no difference in the association based on recanalization status, and the study by Bennett et al, 9 which showed the association was strongest in patients with poor recanalization (mTICI < 2b).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Studies concluded the relationship between short‐term systolic BPV and poor clinical outcomes was influenced by recanalization status following EVT, as determined by the modified Thrombolysis in Cerebral Infarction (MTICI) scores. In five separate studies, the association was strongest for patients with successful recanalization (mTICI 2b or 3) 11‐14,17 . However, this is in contrast with both Anadani et al's 7 study, which found no difference in the association based on recanalization status, and the study by Bennett et al, 9 which showed the association was strongest in patients with poor recanalization (mTICI < 2b).…”
Section: Discussionmentioning
confidence: 83%
“…The majority of the patients had large vessel occlusion of the anterior circulation. NIHSS score at admission ranged from 12 11 to 19, 12 whereas the ASPECTS score at admission ranged from 6 9 to 9 7 . The onset of stroke symptoms to groin puncture time was mentioned in five studies 7,11‐14 and ranged from 154 min to 531 min.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was particularly consistent in subjects with complete recanalization and no history of premorbid hypertension. Another retrospective study from Taiwan showed that the uncontrolled elevation of the blood pressure in the immediate first 6 h after a successful mechanical thrombectomy is an important factor in the final clinical outcome [ 17 ••]. The study found that 50% of the subjects that underwent to a successful recanalization were able to be functionally independent at 90 days.…”
Section: Management Of the Blood Pressure In Acute Ischemic Stroke Immediately After Successful Endovascular Recanalizationmentioning
confidence: 99%